Expression of foraging and Gp‐9 are associated with social organization in the fire ant Solenopsis invicta. Issue 1 (14th October 2014) - Lucas, C.; Nicolas, M.; Keller, L.
Abstract The aim of this study was to investigate levels of expression of two major genes, the odorant binding protein Gp‐9 (general protein‐9) and foraging, that have been shown to be associated with behavioural polymorphisms in ants. We analysed workers and young nonreproductive queens collected from nests of the monogyne (single reproductive queen per nest) and polygyne (multiple reproductive queens) social forms of Solenopsis invicta. In workers but not young queens, the level of foraging expression was significantly associated with social form and the task performed (ie localization in the nest or foraging area). The level of expression of Gp‐9 was also associated with social form and worker localization. In addition there was a higher level of expression of the Gp‐9b allele compared with the Gp‐9B allele in the heterozygote workers and the young nonreproductive queens. Finally, in the polygyne colonies the level of expression of foraging was not significantly associated with the Gp‐9 genotype for either workers or young nonreproductive queens, suggesting that both genes have independent non‐epistatic effects on behaviour in S. invicta.